Comparative efficacy of targeted systemic therapies for pruritus in moderate-to-severe atopic dermatitis without topical treatment: a network meta-analysis - Mei Xiong; Qiaoli Gao; Hu Ren; Tingting Zhong (Taylor & Francis Group, 2024)
Background Chronic pruritus is the most prevalent and severe symptom of atopic dermatitis (AD).Objective This network meta-analysis aims to assess the comparative efficacy of systemic targeted monotherapies in alleviating pruritus among adults and adolescents with moderate-to-severe AD.Methods Data were collected from phase 3/4 randomized controlled trials (RCTs) published until 24 August 2024, focusing on targeted therapies for moderate-to-severe AD. The outcome measure was the proportion of patients achieving a ≥ 4-point improvement from baseline on the Pruritus Numerical Rating Scale (NRS). This analysis included both primary endpoints (week 12 or week 16) and secondary endpoints (weeks 2, 4, and 8).Results Eleven reports comprising 16 studies with 8,462 participants were included. At all time points examined, targeted therapies demonstrated statistically significant efficacy over placebo, with upadacitinib 30 mg showing the highest response rate. The next most effective treatments at the primary endpoint were abrocitinib 200 mg, upadacitinib 15 mg, dupilumab 300 mg, and lebrikizumab 250 mg. Cumulative ranking probabilities at secondary endpoints varied based on time points.Conclusion Targeted therapies, particularly upadacitinib 30 mg, showed significant advantages in managing moderate-to-severe AD pruritus. Further direct comparative trials are needed for conclusive evidence.